A Novel Visual Cryptography Scheme - Jena, D.; Jena, S.K. (2009 International Conference on Advanced Computer Control, 2009)
Visual cryptography is a new cryptographic technique which allows visual information (pictures, text, etc.) to be encrypted in such a way that the decryption can be performed by human, without any decryption algorithm. Here we propose a data hiding in halftone images using conjugate ordered dithering (DHCOD) algorithm which is a modified version of data hiding in halftone images using conjugate error diffusion technique (DHCED). We use this DHOCD algorithm for proposing a new three phase visual cryptography scheme. DHCOD technique is used to hide an binary visual pattern in two or more ordered dither halftone images, which can be from the same or different multi-tone images. In proposed scheme we shall generate the shares using basic visual cryptography model and then embed them into a cover image using a DHCOD technique, so that the shares will be more secure and meaningful.